Review of Patents and Commercial Opportunities Involving Mesenchymal Stromal Cells (MSCs) Therapies in Osteoarthritis - Viswanathan, Sowmya; Gomez-Aristizabal, Alejandro (Recent Patents on Regenerative Medicine, 2014)
Osteoarthritis (OA) is a degenerative joint disease that affects cartilage, subchondral bone, the synovium and synovial fluid and has limited treatment options. With an ageing population and growing health economic costs, novel treatment options for OA are urgently needed. Mesenchymal stromal cells (MSCs) with their demonstrated abilities to modulate pain and inflammation, and with their ability to contribute to chondrocyte differentiation and proliferation are therefore being investigated globally for their potential to provide novel treatment options for OA patients. In this paper, we review the preclinical studies and early clinical trials, and the patent landscape for the use of MSCs for the treatment of OA.
Keywords: Cartilage